Governance and policy in sport organizations - Hums, Mary A.; MacLean, Joanne C. (Arizona : Holcomb Hathaway, Publishers, 2009)
This book introduces you to the power and politics of sport organizations. You will learn the basics of managerial activities necessary for governance and policy development in sport organizations, as well as the structure and function of the various organizations with which you will work and interact when you enter the workforce. You will discover where the power lies in an organization or industry segment and how individual sport organizations fit into the greater industry. Current policy issues and the ethical questions they raise are also addressed. Designed to encourage you to integrate management theory with governance and policy development practices, the second edition of this book provides you with an overview of the sport industry that will help you understand your place in it as a future sport management professional
Introduction to sport governance -- Managerial activities related to governance -- Strategic management and policy development -- Ethics in sport organizations -- Scholastic sport -- Amateur sport in the community -- Campus recreation -- Intercollegiate athletics -- The Major games in amateur sport -- Olympic sport -- Paralympic sport -- North American professional sport -- International professional sport -- The Future of sport governance
Includes bibliographical references and index.
Keywords: SPORTS ADMINISTRATION